Limited Associations Between 5-HT Receptor Gene Polymorphisms and Treatment Response in Antidepressant Treatment-Free Patients With Depression - Ochi, Taichi; Vyalova, Natalya M.; Losenkov, Innokentiy S.; Paderina, Diana Z.; Pozhidaev, Ivan V.; Loonen, Anton J. M.; Simutkin, German G.; Bokhan, Nikolay A.; Ivanova, Svetlana A.; Wilffert, Bob (Frontiers in Pharmacology, 2019)
Major depressive disorder has become a prominent cause of disability, as lifetime prevalence has increased to ~15% in the Western world. Pharmacological effects of serotonin (5-hydroxytryptamine, 5-HT) are mediated through 5-hydroxytryptamine receptor (5-HTR) binding. Serotonin regulation of amygdala activity is attained through activation of three 5-HT2 family receptor subtypes, 5-HT2A, 5-HT2B, and 5-HT2C. Specifically, HT2A and the HT2C receptors have similar gross cerebral distribution and function, with higher constitutive activity found in HT2C than in HT2A. We investigated the possible association of 5-HTR gene polymorphisms to specific and non-specific antidepressant treatment responses in treatment-free patients in Siberia. 156 patients, aged between 18-70 years and clinically diagnosed with depressive disorders, were treated with antidepressants for four weeks. Patients were genotyped for a subset of 29 SNPs from the following 5-HT Receptor genes: HTR1A, HTR1B, HTR2A, HTR2C, HTR3A, HTR3B and HTR6. Primary outcome was measured by differences in Hamilton Depression Rating Scale (ΔHAM‐D 17) scores between baseline/week two, week two/week four and baseline/week four. Univariate linear regression was initially conducted to determine the 5-HTR SNPS to be studied within the multiple linear regression. Multiple linear regression analyses over the three time periods was conducted for ΔHAM‐D 17 with independent factors including: age, gender, depression diagnosis, antidepressant treatment and selected 5-HTR SNPs. We found improved ∆HAM-D 17 was found in patients taking tricyclic antidepressants (0 – 4 weeks: B = 4.85, p = 0.0002; 0 – 2 weeks: B = 3.58, p = 0.002) compared to patients taking SSRIs. Over the course of study, significant associations between 5-HT receptors SNPs and antidepressant response were not identified.